2022
DOI: 10.3389/fgwh.2022.838961
|View full text |Cite
|
Sign up to set email alerts
|

Improving Menstrual Health Literacy Through Life-Skills Programming in Rural Ethiopia

Abstract: Despite its cultural and biological importance, limited knowledge about menstruation and cultural taboos in many contexts mean that menarche often brings fear and stigma. In Ethiopia, the context of this paper, lack of knowledge and the stigma around menstruation create challenges for adolescent girls related to menstrual hygiene management and their reproductive health more broadly. This paper uses a cluster-randomized controlled trial (cRCT), with 97 communities (kebeles) randomly assigned to treatment or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…These results are in line with school-based study programs in Thailand ( 24 ), India ( 6 ), and the Netherlands ( 25 ). In Ethiopia, these findings are also similar to Baird et al ( 14 ) which showed significant progress in the knowledge of menstrual hygiene skills and reproductive health issues ( 16 ). Moreover, in India, the outcome also aligns with the findings of Sukumar et al ( 39 ), which showed significantly improved life skill scores ( 39 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results are in line with school-based study programs in Thailand ( 24 ), India ( 6 ), and the Netherlands ( 25 ). In Ethiopia, these findings are also similar to Baird et al ( 14 ) which showed significant progress in the knowledge of menstrual hygiene skills and reproductive health issues ( 16 ). Moreover, in India, the outcome also aligns with the findings of Sukumar et al ( 39 ), which showed significantly improved life skill scores ( 39 ).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Pradeep et al ( 1 ) found that 91.6% of students in India reported improved awareness of life skills after participating in life skills training. Furthermore, studies conducted in Ethiopia by Malango and Hegena ( 11 ), Tesema et al ( 12 ), and Baird et al ( 13 ) showed that open parent discussions to develop SRH life skills had established positive longer-term impacts and increased student participation by 25.7, 24.5, and 8.2%, respectively ( 11 13 ). In North and East Ethiopia, a gender transformative life skills intervention program was conducted, demonstrating a significant improvement in knowledge of menstruation and its hygiene ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…School-based education is suggested by several researchers as a tool to address low menstrual literacy [ 9 , 31 ]. Schools are useful sites for the dissemination of knowledge about menstrual health as they are considered a trusted source of information [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menstrual education before menarche might contribute to girls feeling more prepared and reducing negative emotions during menarche. However, this alone does not make shame or fear disappear, nor eliminate the taboo or social restrictions as menstrual experiences are shaped by sociocultural context [ 31 ] and the immediate environment of young people has a strong influence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%